FAKTOR-FAKTOR KESULITAN BELAJAR DARING PADA PELAJARAN DASAR DESAIN SISWA KELAS XSEKOLAH MENENGAH KEJURUAN - Ayu Puji Lestari (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2023)
The purpose of this research is descriptively to determine the factors of internal and external learning difficulties experienced by students in bassic design subjects at SMKN 4 Yogyakarta. This research is quantitative descriptive. Data collection instruments include: questionnaires and documentation. The results of the validity test using product moment corelation analysis, and reliability testing using cronbach’s alpha. The data analysis technique used descriptive analysis by looking for the mean, median, mode, and standard deviation values. Research results show that: 1) The factors of online learning difficulties in basic design subjects for class x fashion at SMKN 4 Yogyakarta in terms of internal factors on indicators of attitude, motivasion, interest in the sufficient category, while indicators of understanding and health in high indicarors; 2) The factors of online learning  difficulties in terms of external factors on indicators of the school environment, and online learning facilities are in the sufficient category, while the indicators of the family environment and study friends are in the high category, thus, the factors of online learning difficulties in the basic lesson design of class x student of SMKN 4 Yogyakarta are influenced by internal and external factors.